Multiplicação in vitro de genótipos de Eucalyptus dunnii maiden - Navroski, Marcio Carlos (2011)
Eucalyptus is a genus of great importance to the economy and production of various goods. Among the species of this genus, Eucalyptus dunnii Maiden stands out the importance, especially for the states of southern Brazil, to present a good growth and resistance to frost. However, this species presents problems for the production of seedlings by cloning, mainly due to the difficulty of rooting. The objective of this research was to assess methodologies for surface disinfection, establishment, multiplication, elongation and rooting in vitro of selected genotypes of Eucalyptus dunnii. The genetic material used in this study were collected in areas of the company Stora Enso, in the county of Alegrete - RS in commercial stands of Eucalyptus dunnii about three years old, originated from the planting of seeds. After 60 days, harvested, shoots were collected from 10 selected genotypes, which were isolated from cuttings. In the laboratory, stem segments were isolated at three positions on the cuttings: top, middle and base portion, which were evaluated in procedures for surface disinfection with sodium hypochlorite. We tested different immersion times in disinfest 1.5% and in another experiment, different concentrations of immersion for 10 minutes. Subsequently, we evaluated the performance of genotypes in in vitro establishing. During multiplication were evaluated concentrations of the growth regulators 6-benzylaminopurine (BAP). At the elongation step there were two experiments, one using gibberellic acid (GA3) in varying concentrations in the presence of alpha-Naphthalene acetic acid (NAA) and BAP, and another using only NAA and BAP. In the rooting phase two experiments were conducted, using an IBA in nutrient medium and another pulse treatment with IBA and vermiculite in a liquid medium, the rooted cuttings were acclimatized in plastic cups. As a result it was possible to establish satisfactory six genotypes, and the phenol oxidation and contamination of the main causes of non-establishment of some genotypes. In the multiplication, BAP in a concentration range between 0.25 and 0.75 mg L-1 (1.11 and 3.33 μM), positively influences the formation of buds, there is a behavior varied depending on genotype. At the elongation is also genotypic influence and the use of NAA at 0.5 mg L -1 (2.69 μM) plus BAP promotes the greatest elongation of shoots. The use of GA3 in the nutritive medium of elongation may be waived, because don t promote elongation of the shoots and cause the formation of callus. AIB added to the ½ MS nutritive medium has no effect on in vitro rooting of Eucalyptus dunnii. for the use of vermiculite associated with ½ WPM liquid nutritive medium after treatment pulse with solution of IBA promote root induction in some cuttings and may be considered in further studies.